2006
DOI: 10.1677/joe.1.06589
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle glucose transporter protein responses to antenatal glucocorticoids in the ovine fetus

Abstract: We investigated the effects of maternal antenatal dexamethasone (Dex) treatment given as a single course (4 doses) or multiple courses (20 doses) on fetal skeletal muscle glucose transporter (GLUT) protein concentrations at 70% of gestation (106 to 107 days with term being 145 to 150 days) in the ovine fetus. Antenatal corticosteroid administration was associated with a decrease in endogenous fetal plasma cortisol concentrations (P<0·05), fetal hyperglycemia (P<0·02) and hyperinsulinemia (P<0·05). These metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…In the late-gestation ovine fetus, insulin and glucocorticoids regulate skeletal muscle GLUT1 expression by increasing the concentrations (39,47). After weaning during the postsuckling phase and beyond into adult stages, there is a decline in GLUT1 expression in most tissues except the brain (30,67,108,112).…”
Section: Regulation Of Glut1 Expressionmentioning
confidence: 99%
“…In the late-gestation ovine fetus, insulin and glucocorticoids regulate skeletal muscle GLUT1 expression by increasing the concentrations (39,47). After weaning during the postsuckling phase and beyond into adult stages, there is a decline in GLUT1 expression in most tissues except the brain (30,67,108,112).…”
Section: Regulation Of Glut1 Expressionmentioning
confidence: 99%
“…Besides placenta, GCs affect glucose transport in a variety of peripheral tissues, such as skeletal muscle, adipocytes, and endothelial cells [149][150][151][152][153][154][155][156][157][158][159][160]. High affinity low capacity GRs have been identified in the placenta of various species, including man, rat, and mouse [17,35,161,162].…”
Section: The Effects Of Glucocorticoids On Placental Glucose Transpormentioning
confidence: 99%
“…Prenatal corticosteroid exposure of mice resulted in programming of the fetus such that the adult progeny exhibited glucose intolerance [170,171]. In addition, repeated courses of maternal corticosteroid administration have been shown to alter fetal glucose homeostasis and hepatic enzyme activity in rats [157,173]. In summary, the effects of glucocorticoids in placental glucose transport mechanisms in not fully understood.…”
Section: The Effects Of Glucocorticoids On Placental Glucose Transpormentioning
confidence: 99%
“…We found a decrease in Akt-1 in preterm animals after exposure to GCs suggesting the major effect of GCs is on growth, whereas Akt-2 did not change after GC exposure. It is possible that transient changes in insulin-signaling protein content in the muscle of preterm baboons could be due to concurrent variations in fetal insulin and/or glucose concentrations after GC exposure (Jellyman et al 2005, Grey et al 2006). However, birth weights were similar within gestational groups and published plasma glucose and insulin levels measured at birth were similar in preterm and term control animals (Blanco et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown decreased levels of GLUT1 and GLUT4 in skeletal muscle of fetal preterm baboons (Blanco et al 2010); these differences might be developmental as glucose homeostasis is controlled by passive diffusion through the placenta during fetal life and insulin stimulated glucose disposal is decreased in-utero. Others have shown perturbations in fetal skeletal muscle glucose transporters in sheep after a single dose of GCs, along with fetal hyperglycemia and hyperinsulinemia (Gray et al 2006). Therefore, information is needed on the precise change in insulin function and signaling at the muscle cell level resulting from fetal exposure to concentrations of corticosteroids in excess of those appropriate for the current stage of maturation.…”
Section: Introductionmentioning
confidence: 99%